PERANCANGAN APLIKASI QUIZ PADA MATA PELAJARAN KOMPUTER DAN JARINGAN DASAR BERBASIS MOBILE - Tiara Indah Wicaksana; Vera Irma Delianti (Universitas Negeri Padang, 2019)
The design of this application describes how an android-based quiz application that can help students in learning. The application made is the application of quiz in Computer and Basic Network subjects in class X. This application contains material, syllabus, and quiz. This quiz has three levels of quiz level, they are easy level, normal level, and hard level. Android-based application designed using the Java programming language and developed using PHP and MySQL as database design and data management. The method used in the design is the waterfall method which consists of system requirements analysis and system design. The interface design consists of a home page, a login page, a subject matter page, a syllabus page and a quiz page. Keywords: Quiz, Computer and Basic Network, Android